2003
DOI: 10.1002/jcla.10078
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of total protein, and total and lipid‐associated serum sialic acid levels in patients with type 2 diabetes mellitus

Abstract: The aim of the present study was to investigate the serum total protein (TP), total sialic acid (TSA), lipid-associated sialic acid (LSA), LSA/TP, and LSA/TP values in type 2 diabetes mellitus (DM) patients. Two study groups (healthy controls and type 2 DM subjects) were examined. For the type 2 DM group, 120 patients (60 females and 60 males) who had been diagnosed and treated for type 2 DM in the Yuzuncu Yil University Hospital, Van, Turkey, were selected consecutively. Forty healthy individuals (20 females … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 8 publications
3
9
0
Order By: Relevance
“…10 Serum total sialic acid was significantly increased in the diabetic group compared to the control group (p<0.001). This is similar to the earlier studies by Balu Mahendran et al, 2013;Ekin et al, 2003;Melidonis et al, 1988;Crook et al, 1993. 11 -13 Elevated level of serum sialic acid is a risk factor for overall mortality in type 2 diabetes mellitus patients.…”
Section: Discussionsupporting
confidence: 93%
“…10 Serum total sialic acid was significantly increased in the diabetic group compared to the control group (p<0.001). This is similar to the earlier studies by Balu Mahendran et al, 2013;Ekin et al, 2003;Melidonis et al, 1988;Crook et al, 1993. 11 -13 Elevated level of serum sialic acid is a risk factor for overall mortality in type 2 diabetes mellitus patients.…”
Section: Discussionsupporting
confidence: 93%
“…Studies had shown that elevated level of SA was significantly associated with pancreatic cancer, colorectal cancer, osteosarcoma, oral squamous cell carcinoma, and other malignancies 18-21. However, it was worth noting that some studies had observed that SA levels was obviously higher in patients with severe infection or Type Ⅱ diabetes compared to healthy people 22, 23. Therefore, when data was enrolled into the present study, any other malignancy, infection, inflammation, diabetes and other correlative factors were eliminated to avoid interference with the finally outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…It also contrasted Ekin et al, [16] which showed no significant effect of diabetes mellitus on serum total protein. However, reports regarding salivary total protein levels in diabetics are controversial, as they have shown higher levels [11,[17][18][19][20], lower levels [20], or comparable levels between diabetics and healthy non-diabetics [21][22][23][24][25].…”
Section: Serum and Salivary Protein Profile In Diabetes Mellitusmentioning
confidence: 55%